2018
DOI: 10.1134/s0006297918030094
|View full text |Cite
|
Sign up to set email alerts
|

Glutamic Acid Signal Synchronizes Protein Synthesis Kinetics in Hepatocytes from Old Rats for the Following Several Days. Cell Metabolism Memory

Abstract: The kinetics of protein synthesis was investigated in primary cultures of hepatocytes from old rats in serum-free medium. The rats were fed mixed fodder supplemented with glutamic acid and then transferred to a regular mixed fodder. The amplitude of protein synthesis rhythm in hepatocytes isolated from these rats increased on average 2-fold in comparison with the rats not receiving glutamic acid supplement. Based on this indicator reflecting the degree of cell-cell interactions, the cells from old rats were no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…Goodwin, 130,131 Gilbert, 132,133 Hildebrandt, 134 and Yates [135][136][137][138] repeatedly emphasized these principles in seminal publications. Brodsky and his coworkers 139,140 continue with key physiological experiments in his 90th year.…”
Section: Further Analytical Refinements At the University Of Vienna Amentioning
confidence: 99%
“…Goodwin, 130,131 Gilbert, 132,133 Hildebrandt, 134 and Yates [135][136][137][138] repeatedly emphasized these principles in seminal publications. Brodsky and his coworkers 139,140 continue with key physiological experiments in his 90th year.…”
Section: Further Analytical Refinements At the University Of Vienna Amentioning
confidence: 99%
“…Furthermore, both glutamine and glutamic acid are integral components of the TCA cycle and are essential constituents of the antioxidant glutathione (Tompkins et al, 2019). It has shown that supplementation with glutamic acid significantly increases protein synthesis in primary cultures of hepatocytes from elderly rats, effectively doubling the rate in comparison to elderly rats not receiving glutamic acid supplementation (Brodsky et al, 2018). Additionally, glutathione, a well-known antioxidant, plays a crucial role in combating free radicals to mitigate oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, glutamine and glutamate participate in the TCA cycle in many forms and are essential constituents of the antioxidant glutathione [42]. It has shown that supplementation with glutamic acid significantly increases protein synthesis in primary cultures of hepatocytes from elderly rats, effectively doubling the rate in comparison to elderly rats not receiving glutamic acid supplementation [4]. Additionally, glutathione, a well-known antioxidant, plays a crucial role in combating free radicals to mitigate oxidative stress.…”
Section: Discussionmentioning
confidence: 99%